SOIL PECULIARITIES OF PEAT MASSIFS OF THE PALSA IN THE HIGH MOUNTAINOUS ARABEL PLATEAU (CENTRAL TIEN-SHAN, KYRGYZSTAN) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2023)
Climate warming may lead to a strong transformation of many cryogenic geosystems of the world. High-mountain permafrost peat palsa-massifs having a relatively small areaare particularly vulnerable. We studied four such massifs, the soils of which are diagnosed asCryosols, within the Arabel Plateau of the Central Tien Shan. It is shown that a unique Ca-Fegeochemical landscape is formed on this territory, where active accumulation of carbonates insoils and micro-watersheds takes place. These landscapes actively participate in the formation ofchemical runoff of rivers, and their function can change greatly in warmer climate.
Keywords: palsa, high mountains, Tien-Shan, Arabel plateau, soil morphology, surface water, pH, electroconductivity.